Schriftexegese als Voraussetzung für Emil Brunners frühe dialektische Eschatologie anhand des Beispiels 1. Joh 1,1–4 - STEINER, Fabienne (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
Dialectical Eschatology Using the Example of 1 John 1:1–4. In my article, I would like to show Emil Brunner’s thoughts and central statements that he makes in his unpublished sermons, mainly in Obstalden Etc., between 1912 and 1924 about dialectical theology. As early as 1916, Brunner uses, for example, dialectical eschatology based on 1 John 1:1–4, and not only in the later discussion with his opposing colleague Karl Barth (1934). A detailed exegesis results in the resolution of what was the scope of this central New Testament text in the early Brunner view. In his sermons, he reflects several modern arguments for his time and defines, for example, the old person now, in this time, as thesis, the new person in eternity as antithesis, and the “Ewigkeitsmensch” in the present time as synthesis.